2009
DOI: 10.1002/jbm.b.31393
|View full text |Cite
|
Sign up to set email alerts
|

Use of chitosan membrane associated with polypropylene mesh to prevent peritoneal adhesion in rats

Abstract: The correction of wall abdominal defects often requires the use of implants such as polypropylene meshes. In spite of presenting good tissue acceptance, these biomaterials can migrate to adjacent viscera, promote enterocutaneos fistulas, tissue adherence and visceral erosions. In this work, the barrier effect of chitosan films associated with polypropylene meshes on adhesion formation experimentally induced in Wistar rats was evaluated. The animals were divided into two groups with 10 animals each. Animals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Mitomycin C(MMC) and chitosan are known to inhibit the proliferation of fibroblast and reduce tissue adhesion. At present, both MMC and chitosan are being used against tissue adhesion in clinical and experimental research and a successful outcome was reported [8][9][10].…”
Section: Introductionmentioning
confidence: 96%
“…Mitomycin C(MMC) and chitosan are known to inhibit the proliferation of fibroblast and reduce tissue adhesion. At present, both MMC and chitosan are being used against tissue adhesion in clinical and experimental research and a successful outcome was reported [8][9][10].…”
Section: Introductionmentioning
confidence: 96%
“…The wide variety of new nanomaterials with multifunctional properties has sparked studies aimed at biological applications such as artificial muscles [14], drug delivery [58], implants [9,10] and drug therapies within the nanomedicine paradigm [11,12]. Very stringent requirements must be satisfied for such applications, especially with regard to biocompatibility and/or biodegradability, in addition to the need of suitable mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The use of chitosan [poly-(β-1/4)-2-amino-2-deoxy-Dglucopyranose] has been described in several preclinical studies and tested in tissue bioengineering of bone (Zhao et al, 2002;Kim et al, 2004;Yoshida et al, 2004;Teng et al, 2008;Yuan et al, 2008;Liu et al, 2009;Xianmiao et al, 2009;Li et al, 2010;Mota et al, 2012;Pu et al, 2012;Zhang et al, 2012;Azevedo et al, 2014;Fan et al, 2014;Rodriguez-Vázquez et al, 2015;Vega-Ruiz et al, 2017) neural tissue (Simoes et al, 2011;Meyer et al, 2016;Ghasemi Hamidabadi et al, 2017;Nawrotek et al, 2017;Zhao et al, 2017) and soft tissue (Gobin et al, 2006;Paulo et al, 2009;Tchemtchoua et al, 2011;Udpa et al, 2013;Zou et al, 2017). Chitosan is a copolymer derived from the alkaline deacetylation of chitin and made of N-acetyl-D-glucosamine and D-glucosamine bonds and β bonds in which glucosamine is the main repeating unit in its structure (Rodriguez-Vázquez et al, 2015).…”
mentioning
confidence: 99%